PENGARUH SUPLEMENTASI MIKRONUTRIEN TERHADAP KEJADIAN DIARE PADA BALITA - Candra, Aryu (Universitas Diponegoro, 2019)
Background : The incidence of diarrhea in clinic and hospitals was still high with 6,547 cases and 8,692 cases. Providing zinc and iron supplementation could enhance the immune system to against infectious diseases. This study aimed to determine the effect of zic and iron supplementation on the incidence of diarrhea in toddler.Method : This study used a quasi experimental design with post test only group design. A total of 44 toddlers aged 2-5 years were divided into 4 groups, namely the control group, zinc supplementation group (10 mg/day), iron supplementation group (7.5 mg/day), and group supplementation of zinc+iron (zinc 10 mg/day and iron 7.5 mg/day) for 8 weeks. Data on duration and frequency of diarrhea, as well as supplementation compliance was collected every weekend. Food intake was obtained by the Semi Quantitative Food Frequency Questionaire (SQ-FFQ) method. Data were analyzed using the One Way ANOVA and Kruskal Wallis tests. Result : The duration of diarrhea in the zinc, iron, zinc + iron supplementation and control groups were 0.73 ± 1.23 days; 1.00 ± 1.41 days; 0.18 ± 0.60 days; and 1.00 ± 1.78 days. The total frequency of diarrhea in the zinc, iron, zinc + iron supplementation and control groups was 2.45 ± 4.28 times 3.18 ± 4.45 times; 0.73 ± 2.41 times; and 3.36 ± 5.94 times. The frequency of diarrhea per day in the zinc, iron, zinc + iron supplementation and control groups were 0.92 ± 1.58 times; 1.18 ± 1.67 times; 0.36 ± 1.21 times; and 0.93 ± 1.59 times. The duration, total frequency and frequency of diarrhea per day between the four groups did not have a significant differences (p> 0.05).Conclution : There were no significant differences between the four groups based on duration, total frequency and frequency of diarrhea per day. However, the zinc+iron supplementation group had the lowest duration and frequency of diarrhea.Keyword : Diarrhea, Zinc Supplementation, Iron Supplementation ABSTRAK Latar Belakang : Angka kejadian diare di puskesmas dan rumah sakit masih tinggi dengan 6.547 kasus dan 8.692 kasus. Pemberian suplementasi seng dan zat besi dapat meningkatkan sistem kekebalan tubuh untuk melawan penyakit infeksi. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian suplementasi seng dan zat besi terhadap kejadian diare pada balita.Metode : Penelitian ini menggunakan desain quasi experimental dengan post test only group design. Sebanyak 44 balita berusia 2-5 tahun yang dibagi menjadi 4 kelompok, yaitu kelompok kontrol, kelompok suplementasi seng (10 mg/hari), kelompok suplementasi zat besi (7,5 mg/hari), dan kelompok suplementasi seng+zat besi (seng 10 mg/hari dan zat besi 7,5 mg/hari) selama 8 minggu. Pengumpulan data durasi dan frekuensi diare, serta kepatuhan suplementasi dilakukan setiap akhir minggu. Asupan makan diperoleh dengan metode Semi Quantitative Food Frequency Questionaire (SQ-FFQ). Data dianalisis menggunakan uji One Way ANOVA dan Kruskal Wallis. Hasil : Durasi diare pada kelompok suplementasi seng, zat besi, seng+zat besi, dan kontrol masing-masing 0,73 ± 1,23 hari; 1,00 ± 1,41 hari; 0,18 ± 0,60 hari; dan 1,00 ± 1,78 hari. Total frekuensi diare pada kelompok suplementasi seng, zat besi, seng +zat besi, dan kontrol masing-masing 2,45 ± 4,28 kali; 3,18 ± 4,45 kali; 0,73 ± 2,41 kali; dan 3,36 ±5,94 kali. Frekuensi diare per hari kelompok suplementasi seng, zat besi, seng+zat besi, dan kontrol masing-masing 0,92 ± 1,58 kali; 1,18 ± 1,67 kali; 0,36 ± 1,21 kali; dan 0,93 ± 1,59 kali. Durasi, total frekuensi dan frekuensi diare per hari antara keempat kelompok tidak terdapat perbedaan yang signifikan (p>0.05).